Electromagnetics Properties of Non-Relativistic Deuteron in Ground State - R. Yosi Aprian Sari; Denny Darmawan (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
Proton-neutron interaction that makes up deuteron is a mixture state of ?13 dan ?13, which are each associated with a state ?=0, ?=1 and ?=2, ?=1. In the proton-neutron interaction, there are particle exchanges of medium range (1 fm≤?≤2 fm) i.e. scalar meson exchange and the long range (?>2 fm) i.e. one pion exchange. The electromagnetic properties of non-relativistic deuteron in the ground state can be found from the coupled differential equation, such as magnetic dipole moment, 〈?D〉=0.856521?? and electrical quadrupole moment, 〈?D〉=0.00291396 b.